Deep Tech Solutions for Emerging Markets - Nedayvoda, Anastasia; Mockel, Peter; Graf, Lana (International Finance Corporation, Washington, DC, 2020)
Deep tech companies aim to address the world’s biggest challenges. These include providing Internet access to the unconnected, reducing greenhouse gas emissions, significantly increasing productivity gains across industries, and helping to solve many other intractable problems, particularly in emerging market and developing economies. A deep tech company brings transformative technology from the lab to the market, and democratized research infrastructure and increased available funding has led to the rise of deep tech companies globally, including in emerging markets. Yet commercialization is critical to realizing the benefits of deep tech solutions, and deep tech firms often struggle to successfully commercialize their breakthroughs. Strengthening local ecosystems and investing in deep technologies are critical to overcoming this common obstacle. As development finance institutions, institutional investors, and private equity and venture capital investors explore longer-term investment strategies, deep tech commercialization offers not a tech-enabled silver bullet but a holistic approach to investing in technology solutions.